Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
No.
Step-by-step explanation:
Substitue x = -5 in the equation 5x - 12 = -5(-x + 13)
You'll eventually get -37=-90
Is this true? No!
No I don't think so..
Answer:
-53
Step-by-step explanation:
Distribute
5 − 1 2 = − 5 ( − +1 3 )
5 − 1 2 = 5 − 6 5
Add 1 2 to both sides of the equation
5x-12=5x-65
5x−12+12=5x−65+12
Simplify
5x=5x-53
Subtract 5x from both sides of the equation
5x=5x-53
5x-5x=5x-53-5x
Simplify
-53
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.